2004
DOI: 10.1111/j.1538-7836.2004.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the assessment of von Willebrand disease prevalence an achievable challenge? The example of the French Basque Country where blood group O and factor XI deficiency are highly prevalent

Abstract: Summary. The diagnosis of type I von Willebrand disease (VWD) is not straightforward because of the absence of a single clear-cut biological criteria and the interference of several acquired conditions on phenotype expression. We illustrate here this challenge with the French Basque population characterised by a marked high frequency in both blood group O and factor XI deficiency. From this example one may question the validity of epidemiological studies reporting on VWD prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…It is noteworthy that patient 3 suffered severe bleeding manifestations. However, other haemostatic abnormalities such as von Willebrand disease or platelet dysfunctions were not tested for [23]. Moreover, this patient showed a substitution in the donor site of intron D (c.324þ7T>C), but without consequence on predicted splicing, since the presence of both Cys122Tyr and c.324þ7T>C mutations results in a similar reduction of FXI activity as the Cys122Tyr mutation alone (patients 2 and 4).…”
Section: Resultsmentioning
confidence: 88%
“…It is noteworthy that patient 3 suffered severe bleeding manifestations. However, other haemostatic abnormalities such as von Willebrand disease or platelet dysfunctions were not tested for [23]. Moreover, this patient showed a substitution in the donor site of intron D (c.324þ7T>C), but without consequence on predicted splicing, since the presence of both Cys122Tyr and c.324þ7T>C mutations results in a similar reduction of FXI activity as the Cys122Tyr mutation alone (patients 2 and 4).…”
Section: Resultsmentioning
confidence: 88%
“…Either Ôa significant bleeding tendency or positive inheritanceÕ was attributed to 10 of the 19 patients excluded by criteria B. Therefore, at least nine of them had no significant bleeding, which raised questions about the specificity of criteria A [1]. An earlier study also found a poor correlation between bleeding and low VWF ) by screening 1218 Italian schoolchildren, nine new subjects were diagnosed with VWD type 1 using a definition somewhat more stringent than criteria A [15], and none of them had significant bleeding over the subsequent 13 years [16].…”
mentioning
confidence: 99%
“…It is interesting to compare the numbers of French Basque patients who satisfy the different criteria with the total numbers in the population expected at each VWF level. The region includes approximately 300 000 persons, 168 000 of whom (56%) should be blood type O [1]. Based on the distribution of VWF levels for type O [2], 23 000 of them would have VWF <50 IU dL -1 (criteria A), 4200 would have VWF <37 IU dL -1 (criteria B), and only one would have VWF <15 IU dL -1 (criteria C).…”
mentioning
confidence: 99%
“…In a referral-based study 50 that used a cutoff limit of < 50% for vWF:Ag concentration as the diagnostic criterion for vWD, the distribution in humans was 87% for type 1 13% for type 2, and 0% for type 3 vWD. 50 The referral-based study reported here also used a < 50% cutoff value and had a distribution of 95% type 1, 5% type 2, and 0% type 3 vWD. In the canine population screened in another study, 28 58% of dogs with vWD were classified with type 1, 29% with type 2, and 13% with type 3.…”
Section: Discussionmentioning
confidence: 98%